2022
DOI: 10.2147/prbm.s363434
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive Leadership and Employee Proactive Behavior: A Cross-Level Moderated Mediation Model

Abstract: Purpose The proactive behavior of employees is one of the key determinants of organizational development in a rapidly changing business environment. While much attention has been paid to the antecedents of employees’ proactive behavior, little is known about the mechanisms that influence their psychological state and work behavior. The aim of this research is to investigate the relationship between inclusive leadership (IL) and proactive behavior, along with mediating role of employee trust and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 54 publications
3
11
0
Order By: Relevance
“…Meanwhile, the predictions of this study regarding inclusive leadership and proactive behaviors are consistent with the results of previous studies: consistently, the more inclusive a leader is, the more frequently followers engage in proactive behaviors (Su et al. , 2023; Chang et al. , 2022; He, 2021; Xu et al.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Meanwhile, the predictions of this study regarding inclusive leadership and proactive behaviors are consistent with the results of previous studies: consistently, the more inclusive a leader is, the more frequently followers engage in proactive behaviors (Su et al. , 2023; Chang et al. , 2022; He, 2021; Xu et al.…”
Section: Discussionsupporting
confidence: 91%
“…(2021) found that inclusive leadership has a positive effect on employees’ proactive behavior, while trust in the leader partially mediates this relationship and climate for inclusion moderates the relationship between trust in the leader and proactive behavior. Chang et al. (2022) showed that inclusive leadership has a significant effect on employees’ proactive behavior, in which employee trust plays a mediating role.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, leader consideration was confirmed to have a positive relationship with follower proactive behavior, consistent with previous results (e.g., Chang et al, 2022; Vogt et al, 2021). However, information sharing had no direct effect.…”
Section: Discussionsupporting
confidence: 89%
“…Leaders who provide support, close relationships, and a psychologically safe work environment enable followers to demonstrate proactive behaviors, such as voice, innovation, and taking charge (Chang et al, 2022). Leaders who treat followers respectfully, with honesty and politeness, and recognize their core needs positively affect follower proactivity (Vogt et al, 2021) Followers who receive appropriate information from a leader perceive themselves as belonging to the organization and feel attached to the organization (Baumeister & Leary, 1995).…”
Section: Leadership and Proactive Behaviormentioning
confidence: 99%